The Right to Be Unheard: Recognition and Enforcement of Anti-Suit Injunctions Issued by Arbitrators in the EU. (26th March 2018) - Marcisz, Paweł; Orzeł-Jakubowska, Aleksandra
Abstract: The article discuses recognition and enforcement of anti-suit injunctions issued by arbitral tribunals in the EU, taking into account limitations on arbitrators' power to issue the injunctions as well as their legal effects in various jurisdictions. We critically evaluate the consistency of the CJEU's approach to anti-suit injunctions as presented in West Tankers and in Gazprom . To this end, we compare effects of anti-suit injunctions from state courts and these from arbitral tribunals on the efficiency of EU law and the fundamental rights that it protects. Special regard is paid to the right to legal protection as enshrined in Article 47 of the Charter of Fundamental Right.